2012
DOI: 10.1007/978-94-007-4546-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Immediate-Type Allergic Asthma due to Potassium Tetrachloroplatinate in Production of Cytotoxic Drugs

Abstract: Allergic immediate-type reactions by halogenated compounds of platinum (Pt) (platinum salts) have been described in workers in precious metal refineries and catalyst productions. In both industries there are exposures to many different Pt compounds. It is believed that the most important allergens are those compounds with the highest number of halide ligands. It is unknown whether sensitizations to compounds with a lower number of halide ligands represent co-sensitizations or are due to cross-reactivity. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Some studies have observed a high level of exhaled NO in sensitized employees [70] or its increase after specific allergen challenge in sensitized employees [68,71,72]. The increase in exhaled NO has been observed 24-48 hours post allergen exposure in the working environment [68].…”
Section: Contribution Of Exhaled No Measurement In Occupational Asthmamentioning
confidence: 89%
See 1 more Smart Citation
“…Some studies have observed a high level of exhaled NO in sensitized employees [70] or its increase after specific allergen challenge in sensitized employees [68,71,72]. The increase in exhaled NO has been observed 24-48 hours post allergen exposure in the working environment [68].…”
Section: Contribution Of Exhaled No Measurement In Occupational Asthmamentioning
confidence: 89%
“…Néanmoins, l'ensemble des données disponibles suggère que la mesure de FE NO peut aider à identifier les asthmatiques non-observants parmi le sous-groupe ayant une valeur de FE NO initialement élevée.Apport de la mesure du NO expiré dans les asthmes en relation avec le travailDans le domaine de la recherche sur la santé respiratoire en milieu professionnel, la mesure de FeNO est de plus en plus souvent intégrée dans la batterie d'examens utilisés et a été réalisée chez des salariés de différents milieux professionnels : salariés exposés à des animaux de laboratoire, aux endotoxines, à des épices, aux isocyanates, au latex ou encore chez des agriculteurs, boulangers, personnel de soins, maîtres-nageurs[68][69][70]. Certaines études ont observé un niveau élevé de NO expiré chez des salariés sensibilisés[70] ou son augmentation après un test de provocation spécifique chez des salariés sensibilisés[68,71,72].L'augmentation du NO expiré a été observée de 24 à 48 heures après l'exposition aux allergènes du milieu professionnel[68]. D'autres études cependant, n'ont pas observé d'association entre la mesure de NO expiré et le résultat de tests de provocation bronchique spécifique ou la concentration en IgE spécifiques pour le latex, les diisocyanates et l'isocyanurate de triglycidyle[73,74] ou d'augmentation de la mesure de NO expiré avec l'augmentation de l'exposition au chrome et au cobalt[75].…”
unclassified
“…SICs are considered the reference standard for the diagnosis of occupational asthma, and, when done in the laboratory, they allow identification of the responsible agent [1,7,8]. [18][19][20] lists all new causes of IOA according to their molecular weight, that is, high (>5-10 kD, usually a protein or glycopeptide) or low, as well as the type of job involved (workplace setting), the number of subjects and their clinical characteristics (age, sex, atopic status, and smoking history when known), associated work-related symptoms (rhinoconjunctivitis and contact urticaria or dermatitis), immunological findings specific to the relevant agent (SPT and sIgE) when done, functional tests used to confirm the diagnosis of asthma (defined by variable airflow obstruction or increased BHR) and work relatedness including monitoring of PEFs at and off work, and finally results of SICs.…”
Section: New Agentsmentioning
confidence: 99%
“…The majority of new causes of IOA were seen with high molecular agents: new enzymes used as detergents [11 && ,12] or food additives [13], arthropods contaminating food (cured ham) [14], earthworms used as aquarium fish food [15 && ], and orange fruit [tree aeroallergen [16] and flavedo (zest) [17 & ]], and only three agents having a low molecular weight (LMW) (spruce wood dust [18], the biocide 4,4-methylene-bismorpholine [19], and the halogenated platinum compound K 2 PtCL 4 [20]). Although savinase is not a truly new agent as it belongs to the subtilisin family, like other enzymes such as maxatase or alcalase, the cases presented here [11 && ,12] were the first cases described with this specific protease enzyme derived from Bacillus amyloliqefaciens.…”
Section: New Agentsmentioning
confidence: 99%
“…9 A few have been associated with the production of specific IgE antibodies, such as complex platinum salts used in platinum refineries or the manufacture of catalysts, 10 with a recent report of cases in workers exposed to platinum salts during the manufacture of cytotoxic drugs. 11 Other examples include rhodium salts (used in electroplating) 12 ; salts of nickel, chrome, and cobalt 13 ; acid anhydrides (used as hardeners in epoxy resins in chemical plants and in powder paints) 14 ; and reactive dyes (used in textiles). 15 However, most low-molecular-weight chemical sensitizers induce asthma through mechanisms that are poorly understood, despite a phenotype suggesting sensitization.…”
mentioning
confidence: 99%